THE IMPACT OF CLASSROOM SEATING ARRANGEMENTS ON STUDENT LEARNING AND ENGAGEMENT - Fayyozjon Azimov (Western European Studies, 2026)
This article presents a comprehensive analysis of classroom seating arrangements and their significant influence on the learning environment, student engagement, academic achievement, and social interaction. As pedagogical approaches evolve from teacher-centered to learnercentered models, the physical arrangement of the classroom has become a crucial factor shaping instructional strategies. This study reviews traditional row seating, group cluster seating, U-shaped arrangements, and modern flexible seating, discussing their impact on communication, motivation, attention span, and classroom discipline. The findings emphasize the necessity for adaptive seating strategies that align with lesson objectives and student needs.
Keywords: classroom environment; seating arrangement; student engagement